Desenvolvimento de uma tecnologia social no Bairro Industrial Xarquinho na cidade de Guarapuava - PR - Lima, Marcio José de (2024)
Social Technologies for social interaction and a list of techniques with methodology that can positively impact society are intended to promote solutions for social inclusion and improvement of the living conditions of the community. A business model that is related to Social Technologies are Cooperatives, especially the popular ones, which aim to constitute themselves as an alternative to the traditional capitalist business model, as Cooperatives have principles that differ from that, such as democratic management, self-management, in that the worker owns the means of production, etc. Another concept related to the research is the Solidarity Economy, which in historical moments, particularly those of crisis such as those experienced due to the Covid-19 pandemic, constitutes an alternative to overcoming capitalist exploitation and entering the labor market by those who are unable enter it. Based on these concepts, the objective of this work is to collaborate with the development of a Social Technology, informally organized as a handicraft cooperative, in a peripheral neighborhood of the city of Guarapuava, from June 2020 to October 2021 through the construction of managerial tools for decision-making, such as the proposition of a business model and the search for partnerships to leverage the enterprise. This technical report had as a methodology adopted by practical works, called Project for Solution of Business Problems/Use of Opportunities (PSPE/AO). The study design was as follows: regarding the methodological approach, it is an applied study, with a qualitative approach, regarding its objective, it is configured as descriptive and exploratory. The object of study was the Cooperativa de Artesanato de Dourados. The technical procedures were bibliographic and documental research and field study. Data collection was carried out through documents, observations and conversations or meetings with the social actors involved. Data analysis comprised document analysis and content analysis. The main results show that this cooperative is linked to the local residents' association and does not have a legal nature, which legally prevents it from executing business acts on its own, which does not occur in the cooperative model, and this can bring to the cooperative members an improvement in working conditions and income from increased sales; it will also contribute to the viability of access to credit and to the promotion notices, so that these workers will actually exercise the self-management of the business, in addition to overcoming other legal impediments. To assist in the proposition of solving the problem studied, management tools were built together with the social actors linked to the Cooperative, namely: the SWOT Matrix (Strengths, Weaknesses, Opportunities and Threats), which allowed the analysis of the problem and the opportunity of the development of Technology Social; the Business Model Canvas, which established the business model through the formalization of the cooperative; and the Executive Summary with which new partnerships were sought and the consolidation of old partnerships, using the new business model. And a model of Bylaws and minutes was created in the case of the decision to formalize the business.